Aspects of the reproductive biology of Zingiber spectabile (Zingiberaceae) - Ferreira Rezende, Kamilla; dos Santos Alves da Silva, Robson; Campos da Silva, Patrícia; Menezes Cordeiro, Maria Helena; Silva, Celice Alexandre (Revista Ceres, 2025)
Ginger (Zingiber spectabile) is cultivated worldwide as a floriculture and landscaping species. Studies on the biology and floral morphology of this species are important for its improvement; however, they are scarce. We investigated the reproductive biology and floral morphology of gingers grown in a germplasm bank. Floral development was monitored during the pre-anthesis and anthesis periods. Floral morphometry, pollen viability, stigmatic receptivity, volume and concentration of nectar sugar, and performance of possible pollinators were evaluated. Ginger flowers had a 24-h durability. Ginger torch is an allogamous species that exhibits floral hercogamy like other Zingiberaceae. Ginger flowers had a 12-h anthesis. During anthesis, floral structures related to reproduction such as the style, stigma, and anther crest continued to develop, increasing floral herkogamy. Pollen viability was above 70% and the stigma remained receptive throughout the anthesis period. Hummingbirds were the only pollinators recorded in the study area that were able to move the anther crest. Fruiting was determined in a natural pollination system. The occurrence of nocturnal anthesis characterized by an increase in the development of reproductive structures and nectar production suggests that the species is adapted to nocturnal visitors.